Penjadwalan Produksi Label Menggunakan Metode Palmer untuk Meminimasi Makespan di CV. PQR - Firdaus, Muhammad Fauzan; Amalia, Akhsani Nur; Widarman, Agung (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
CV. PQR is a company operating in the printing sector. The main printing produced at the company is labels for vegetable products. When producing labels, the company always strives to produce quality products that reach consumers on time. In order for the production process to run, good production scheduling is needed. This research aims to schedule label production on CV. PQR. The label production scheduling method used is Palmer. The results of production scheduling calculations using the Palmer method have a job sequence of 10-9-8-7-6-4-5-3-2-1 and produce a makespan value of 248740 seconds or 69.0944 hours and require 8.6368 days to complete everything. jobs. There is a time difference between the company's initial condition production scheduling and production scheduling using the Palmer method, namely 13160 seconds or 3.6556 hours or 0.45695 days. So the Palmer method can minimize delivery delays